Nanocompósitos eletroativos de poli-o-metoxianilina e polissacarídeos naturais - Eiras, Carla; Passos, Ionara Nayana Gomes; Brito, Ana Cristina Facundo de; Santos Júnior, José Ribeiro dos; Zucolotto, Valtencir; Oliveira Jr, Osvaldo N.; Kitagawa, Igor L. [UNESP]; Constantino, Carlos J. L. [UNESP]; Cunha, Helder Nunes da (Sociedade Brasileira de Química, 2007)
In this work we take advantage of the polyelectrolyte character of some Brazilian native gums to fabricate electrically conductive, nanostructured films. The gums Sterculia urens, (caraia), Sterculia striata (chicha) or Anadenanthera macrocarpa Benth were assembled in conjunction with poly(o-methoxyaniline) (POMA) in the form of layered nanostructured films using the layer-by-layer (LbL) technique. All the LbL films displayed a well-defined electroactivity, as confirmed via cyclic voltammetry. In comparison to POMA LbL films fabricated with conventional polyelectrolytes (viz. poly(vinyl sulfonic acid)-PVS), the presence of the gums in the LbL films increased remarkably the electrochemical stability of the films.
Electroactive nanocomposites made of poly (o-methoxyaniline) and natural polysaccharides
Keywords: natural gums; poly-o-methoxyaniline; layer-by-layer films